Mutsu Munemitsu and his time - Hisahiko, Okazaki (Japan Publishing Industry Foundation for Culture, 2018)
Toward the end of the Tokugawa shogunate, Mutsu Munemitsu was ousted from his home Kisu-han as a result of his father’s defeat in a power struggle. To avenge this, Mutsu bolstered his talent to become a man of “genius and learning in equal measure.” He joined the Kobe Naval Training Center founded by Katsu Kaishu and, later, Kaientai, a trading and shipping company and private navy founded and managed by Sakamoto Ryoma before the Meiji Restoration was accomplished.